A new battery process technology inspired by partially carbonized polymer binders. (January 2020) - Li, Zeheng; Ji, Jiapeng; Wu, Qiang; Wei, Di; Li, Siyuan; Liu, Tiefeng; He, Yi; Lin, Zhan; Ling, Min; Liang, Chengdu
Abstract: There is always trade-off among the functions of active materials, conductive additives and polymer binders. The balance is broken due to the emerging of high energy density silicon anode with low conductivity and huge volume variations. Herein, we explored a bicomponent electrode system through partial carbonization of nature polymers to solve the dilemma. Along with the carbonization process, the hydrogen bonding sites are gradually reduced, however, the dispersion force increases due to the decrease of the surface tension. Meanwhile, the electronic conductivity increases ascribed to the electron delocalization over the chain and in the length of the poly-conjugation. The balance of the binding strength and conductivity is tailored through the control of carbonization temperature. The optimum carbonization condition was revealed at 250 °C in air atmosphere. The partially carbonized polymer acts as both binder and conductive additive for the Si anode. As expected, the carbonized binding system can cycle the silicon anode stably without any other conductive additives. This partial carbonization binder is feasible to scale up due to the facile heat treatment process, which provides a new strategy for designing next-generation high-capacity batteries. Graphical abstract: Herein, a partially carbonized binder strategy is proposed for high-performance Si anodes. The electronic conductivity of the binder is enhanced while the binding capability is sufficient. The bicomponent Si anode with partially carbonized binder shows the better electrochemical performance than the traditional tricomponent system Si anode at the high Si content (90 wt%) and high current density (1.39 A g −1 ). Image 1 Highlights: Partially carbonized polymer binder was obtained by simple heat treatment process in the air. A new battery process technology realized by partially carbonized polymer binder. Partially carbonized binding system can cycle the Si anode stably without any other CAs. Universality of the partially carbonized binder strategy was confirmed. Bicomponent Si electrode shows much better electrochemical performance.